Makna Perjuangan Doctor Strange untuk Mempertahankan Semesta dari Ancaman Kejahatan - Putri Iranda Tedy; Ani Yuningsih (Bandung Conference Series: Journalism, 2024)
Abstract. Film as one of the arts and entertainment media whose pace of development is accelerating from time to time. Film is also a communication medium that can be enjoyed by all circles of society. In films, there are messages and meanings that are then interpreted by the audience. Doctor Strange In The Multiverse Of Madness is a superhero film produced by Marvel Studios directed by Sam Raimi as the director of Multiverse of Madness replacing Scott Derrickson. Doctor strange in The Multiverse of Madnes itself, of course, has many signs or symbols that can be analyzed, one of which is related to the meaning of struggle. In this study, a qualitative method approach was used. With the Constructivist paradigm. By using Roland Barthes' semiotic theory based on the three aspects of denotation, connotation and myth, based on these aspects, the meaning of struggle emerged in the film Doctor Strange In The Multiverse Of Madness. Abstrak. Film sebagai salah satu seni dan media hiburan yang laju perkembangannya semakin cepat dari masa ke masa. Film juga merupakan media komunikasi yang dapat dinikmati semua kalangan masyarakat. Dalam film, terdapat pesan dan makna yang kemudian ditafsirkan oleh penontonnya. Film Doctor Strange In The Multiverse Of Madness adalah sebuah film superhero yang di produksi oleh Marvel Studios yang di sutradarai oleh Sam Raimi sebagai sutradara Multiverse of Madness menggantikan Scott Derrickson. Pada film Doctor strange in The Multiverse of Madnes sendiri tentu saja memiliki banyak tanda atau symbol yang dapat dianalisis salah satunya adalah yang berkenaan dengan makna perjuangan . Dalam penelitian ini digunakan pendekatan metode kualitatif. Dengan paradigma Kontruktivis. Dengan menggunakan teori semiotika Roland Barthes berdasarkan ketiga aspek denotasi, konotasi dan mitos , berdasarkan aspek tersebut maka munculah makna perjuangan yang ada pada film Doctor Strange In The Multiverse Of Madness.